2015
DOI: 10.1016/j.neuroscience.2014.12.083
|View full text |Cite
|
Sign up to set email alerts
|

Developmental decline in modulation of glutamatergic synapses in layer IV of the barrel cortex by group II metabotropic glutamate receptors

Abstract: Previously, we demonstrated that group II mGluRs reduce glutamate release from thalamocortical synapses during early postnatal development (P7–11). To further examine the role of group II mGluRs in the modulation of somatosensory circuitry, we determined whether group II mGluRs continue to modulate thalamocortical synapses until adulthood and whether these receptors also modulate intra-cortical synapses in the barrel cortex. To address these issues, we examined the effect of the group II mGluR agonists on thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In cortical L4, adenosine suppresses excitatory thalamocortical input to both L4 inhibitory and excitatory neurons (Fontanez and Porter 2006;Mateo and Porter 2015). In the neocortex, our previous (van Aerde et al 2015) and present work reveals a more selective role for adenosine in modulating neuronal excitability and neurotransmission.…”
Section: The Role Of Adenosine In Modulating Barrel Cortex Functionsupporting
confidence: 59%
See 1 more Smart Citation
“…In cortical L4, adenosine suppresses excitatory thalamocortical input to both L4 inhibitory and excitatory neurons (Fontanez and Porter 2006;Mateo and Porter 2015). In the neocortex, our previous (van Aerde et al 2015) and present work reveals a more selective role for adenosine in modulating neuronal excitability and neurotransmission.…”
Section: The Role Of Adenosine In Modulating Barrel Cortex Functionsupporting
confidence: 59%
“…In the primary somatosensory (barrel) cortex of rodents, layer 4 (L4) neurons are the major targets of thalamocortical afferents from the ventroposterior medial nucleus of thalamus (Bosman et al 2011;Feldmeyer 2012;Feldmeyer et al 2013). Previous work has shown that thalamocortical excitation of L4 excitatory and inhibitory neurons is down-regulated by presynaptic adenosine A1 receptors in juvenile and adult mouse barrel cortex (Fontanez and Porter 2006;Mateo and Porter 2015). However, the effect of adenosine on the local intracortical synapses between L4 excitatory and inhibitory neurons has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The electrophysiological properties of RVLM neurons and their responses to angiotensin II differ between WKYs and SHRs, even in the neonatal stage [21]. mGluRs, especially postsynaptic ones, do not exhibit any function at younger (juvenile) stages in some cases [22][23][24] but regulate various neuronal functions at different developmental stages [25][26][27][28][29][30][31][32][33][34]. Furthermore, mGluR2/3 agonists hyperpolarize neurons in normotensive rats [35], while the agonists effects seemed to be attenuated in adult SHRs (authors' observation).…”
Section: Introductionmentioning
confidence: 99%
“…The repeated exposure of nicotine during adolescence may affect the maturation of mice insular circuitry and lead to changes in the insular circuitry that may last for a lifetime. It has been shown that the enhanced spike-timing dependent plasticity caused by adolescent nicotine exposure in the rat prefrontal layer V PNs was mediated by a long-term decrease in the expression of synaptic metabotropic glutamate receptor 2 (mGluR2) [ 31 ], which was present in presynaptic terminal and reduces excitatory synaptic transmission [ 32 , 33 ]. Thus, it is possible that adolescent nicotine exposure reduces synaptic mGluR2 expression in the mice insular cortex at later life, which may increase synaptic potentiation in insular layer V PNs.…”
Section: Discussionmentioning
confidence: 99%